Age-Adjusted D-Dimer in the Prediction of Pulmonary Embolism: Systematic Review and Meta-analysis - Kenneth Iwuji; Hasan Almekdash; Kenneth M. Nugent; Ebtesam Islam; Briget Hyde; Jonathan Kopel; Adaugo Opiegbe; Duke Appiah (SAGE Publishing, 2021)
Background: Pulmonary embolism (PE), depending on the severity, carries a high mortality and morbidity. Proper evaluation, especially in patients with low probability for PE, is important to avoid unnecessary diagnostic testing. Objective: To review the diagnostic utility of conventional versus age-adjusted D-dimer cutoff values in patients 50 years and older with suspected pulmonary embolism. Methods: Systematic review with univariant and bivariant meta-analysis. Data sources: We searched PubMed, MEDLINE, and EBSCO for studies published before September 20th, 2020. We cross checked the reference list of relevant studies that compares conventional versus age-adjusted D-dimer cutoff values in patients with suspected pulmonary embolism. Study selection: We included primary published studies that compared both conventional (500 µg/L) and age-adjusted (age × 10 µg/L) cutoff values in patients with non-high clinical probability for pulmonary embolism. Results: Nine cohorts that included 47 720 patients with non-high clinical probability were included in the meta-analysis. Both Age-adjusted D-dimer and conventional D-dimer have high sensitivity. However, conventional D-dimer has higher false positive rate than age-adjusted D-dimer. Conclusion: Age-adjusted D-dimer cutoffs combined with low risk clinical probability assessment ruled out PE diagnosis in suspected patients with a decreased rate of false positive tests.